P–T–t–D record of crustal‐scale horizontal flow and magma‐assisted doming in the SW Mongolian Altai. (6th February 2015) - Broussolle, A.; Štípská, P.; Lehmann, J.; Schulmann, K.; Hacker, B. R.; Holder, R.; Kylander‐Clark, A. R. C.; Hanžl, P.; Racek, M.; Hasalová, P.; Lexa, O.; Hrdličková, K.; et al.
ABSTRACT The Chandman massif, a typical structure of the Mongolian Altai, consists of a migmatite–magmatite core rimmed by a lower grade metamorphic envelope of andalusite and cordierite‐bearing schists. The oldest structure in the migmatite–magmatite core is a subhorizontal migmatitic foliation S1 parallel to rare granitoid sills. This fabric is folded by upright folds F2 and transposed into a vertical migmatitic foliation S2 that is syn‐tectonic, with up to several tens of metres thick granitoid sills. Sillimanite–ilmenite–magnetite S1 inclusion trails in garnet constrain the depth of equilibration during the S1 fabric to 6–7 kbar at 710–780 °C. Reorientation of sillimanite into the S2 fabric indicates that the S1–S2 fabric transition occurred in the sillimanite stability field. The presence of cordierite, and garnet rim chemistry point to decompression to 3–4 kbar and 680–750 °C during development of the S2 steep fabric, and post‐tectonic andalusite indicates further decompression to 2–3 kbar and 600–650 °C. Widespread crystallization of post‐tectonic muscovite is explained by the release of H2O from crystallizing partial melt. In the metamorphic envelope the subhorizontal metamorphic schistosity S1 is heterogeneously affected by upright F2 folds and axial planar subvertical cleavage S2. In the north, the inclusion trails in garnet are parallel to the S1 foliation, and the garnet zoning indicates nearly isobaric heating from 2.5 to 3 kbar and 500–530 °C. Cordierite contains crenulated S1 inclusion trails and has pressure shadows related to the formation of the S2 fabric. The switch from the S1 to the S2 foliation occurred near 2.5–3 kbar and 530–570 °C; replacement of cordierite by fine‐grained muscovite and chlorite indicates further retrogression and cooling. In the south, andalusite containing crenulated inclusion trails of ilmenite and magnetite indicates heating during the D2 deformation at 3–4 kbar and 540–620 °C. Monazite from a migmatite analysed by LASS yielded elevated HREE concentrations. The grain with the best‐developed oscillatory zoning is 356 ± 1.0 [±7] Ma (207Pb‐corrected 238U/206Pb), considered to date the crystallization from melt in the cordierite stability 680 °C and 3.5 kbar, whereas the patchy BSE‐dark domains give a date of 347 ± 4.2 [±7] Ma interpreted as recrystallization at subsolidus conditions. The earliest sub‐horizontal fabric is associated with the onset of magmatism and peak of P–T conditions in the deep crust, indicating important heat input associated with lower crustal horizontal flow. The paroxysmal metamorphic conditions are connected with collapse of the metamorphic structure, an extrusion of the hot lower crustal rocks associated with vertical magma transfer and a juxtaposition of the hot magmatite–migmatite core with supracrustal rocks. This study provides information about tectono‐thermal history and time‐scales of horizontal flow and vertical mass and heat transfer in the Altai orogen. It is shown that, similar to collisional orogens, doming of partially molten rocks assisted by syn‐orogenic magmatism can be responsible for the exhumation of orogenic lower crust in accretionary orogenic systems.